Review: the role of vitamin D in nervous system health and disease. - DeLuca, G; Kimball, S; Kolasinski, J; Ramagopalan, S; Ebers, G (2013)
Vitamin D and its metabolites have pleomorphic roles in both nervous system health and disease. Animal models have been paramount in contributing to our knowledge and understanding of the consequences of vitamin D deficiency on brain development and its implications for adult psychiatric and neurological diseases. The conflation of in vitro, ex vivo, and animal model data provide compelling evidence that vitamin D has a crucial role in proliferation, differentiation, neurotrophism, neuroprotection, neurotransmission, and neuroplasticity. Vitamin D exerts its biological function not only by influencing cellular processes directly, but also by influencing gene expression through vitamin D response elements. This review highlights the epidemiological, neuropathological, experimental and molecular genetic evidence implicating vitamin D as a candidate in influencing susceptibility to a number of psychiatric and neurological diseases. The strength of evidence varies for schizophrenia, autism, Parkinson's disease, amyotrophic lateral sclerosis, Alzheimer's disease, and is especially strong for multiple sclerosis.